IoT-Based Reverse Vending Machine (RVM) for recycle station - Mohd Adzaharee, Muhammad Sallehuddin; Ahmad, Afandi; Mohd Nadzri, Muhammad Muzakkir (Penerbit UTHM, 2021)
Recycle our daily solid waste is a sustainable and effective way to reduce the problem of landfills saturation and pollution. In urban areas and smart cities, the reverse vending machine (RVM) recycle concept has been introduced to encourage recycle habits and increase awareness among the community. In this project, an Internet of Things (IoT)-based RVM for recycle station has been developed to resolve these issues. The proposed prototype consists of three main parts; input (the proximity inductive/capacitive and weight sensors) to detect three types of waste material and weighted the collection material, process (micro-controller Arduino Mega and NodeMCU) to process the data received from the sensor and transmit data to IoT platform via Wireless-Fidelity (WiFi) and output (Blynk IoT platform and InterIntegrated Display (I2C) Liquid Crystal Display (LCD) as a graphical user interface (GUI)) to notify the workers and exhibit the rewarding system. Evaluation of the prototype shows that it is successfully to detect three types of waste materials which are aluminium can, plastic and glass, and notify the users when the RVM storage is full and show the reward system via I2C LCD display.